Robots should be seen and not heard…sometimes: Anthropomorphism and AI service robot interactions. Issue 12 (14th August 2021) - Letheren, Kate; Jetten, Jolanda; Roberts, Jonathan; Donovan, Jared
Abstract: There is a growing need to understand how consumers will interact with artificially intelligent (AI) domestic service robots, which are currently entering consumer homes at increasing rates, yet without a theoretical understanding of the consumer preferences influencing interaction roles such robots may play within the home. Guided by anthropomorphism theory, this study explores how different levels of robot humanness and social interaction opportunities affect consumers' liking for service robots. A review of the extant literature is conducted, yielding three hypotheses that are tested via 953 responses to an online scenario‐based experiment. Findings indicate that while consumers prefer higher levels of humanness and moderate‐to‐high levels of social interaction opportunity, only some participants liked robots more when dialogue (high‐interaction opportunity) was offered. Resulting from this study is the proposed Humanized‐AI Social Interactivity Framework. The framework extends previous studies in marketing and consumer behavior literature by offering an increased understanding of how households will choose to interact with service robots in domestic environments based on humanness and social interaction. Guidelines for practitioners and two overarching themes for future research emerge from this study. This paper contributes to an increased understanding of potential interactions with service robots in domestic environments.